Observations on the Elements of the Bankura Forest Oivision, West Bengal - Das, S. R. (Indian Forester, 1982)
Observations on the vegetatlon of the Bankura Forest Division are presented. Physiographically, the Bankura district may be divided into two parts, east and west. The hloristic pattern is not uniform in both the parts. Trees, shrubs and woody climbers occurring in general all over the division are enumerated. Differences in the distribution of some trees and elements of shrubby undergrowth are discussed.